Optimization of sugar assimilation test for identification of clinically isolated yeast - Othman, Afaf Alani Che (2004)
The study to developed the sugar assimilation test for identification of clinically isolated yeast was done using the swab lawning method and the method of incorporation of suspension on to medium. The result obtained, showed that the swab lawning method was not feasible to be used for identifying clinically isolated yeast based on the sugar assimilation test However, the method of incorporation of suspension on medium was comparatively better and was carried out by optimizing the test by varying the sugar concentration, medium pH and incubation temperature. Candida spp. were screened using 14 types of sugars. The optimized conditions for identification purpose was 20% ( w/v) of sugar concentration, medium pH of 5.6 and the incubation temperature of 30°C for both Candida albican and Candida tropicalis. Under these optimized conditions for identification, Candida a/bican did not utilized cellobiose, whereas Candida tropica/is utilized cellobiose. But the optimum growth conditions for both species were same. Therefore the method of incorporation of suspension under the optimized conditions may be used in the identification of clinically isolated yeast especially in differentiating Candida a/bican and Candida tropical is.